Nexus Between Treasury Single Account, Revenue Generation, Transparency and Accountability: Evidence from Nigerian (British Journal of Multidisciplinary and Advanced Studies, 2023)
This study assessed the impact of treasury single account (TSA) on revenue generations, transparency and accountability: evidence from Nigerian federal road safety corps. Correlational research design was adopted and one hundred and twenty-five copies of questionnaire were distributed to staff of federal road safety corps in Niger state, Nigeria. The study employed ordered logit regression to analyze the data obtained and the findings revealed that TSA improves revenue generation, promote transparency and accountability. It was recommended that federal government should conduct periodic checks on all MDAs so as to enforce the implementation of the TSA policy in all their revenue generation activities.